O idoso e a embalagem : premissas para projeto gráfico - Moura, Claudia Weber (2017)
This study seeks to define premises and parameters for graphic design on packaging of products sold in retail that consider the elderly public. The topics covered in the theoretical review are related to aging, the characteristics of the elderly as consumers, the packaging and the relationship of the elderly with the packaging of the products they consume. For the development of the researches, a qualitative method was used with interviews with three groups: older consumers; graphic designers with experience in packaging; designers over the age of 60. The researches aimed to investigate how the elderly relate to the communication found in packaging, the experience of the designers in their projects and the relation of such issues to the aging process. At the end of the study, it was possible to understand that, in order for the elder to experience their aging dealing with its consequences, it is necessary that the environment, in general, and the packaging, in a specific way, be prepared to serve them. In order to achieve this, the project for the graphic design on the packaging must consider the aging process in its three aspects: biological, social and psychological; as well as a careful look at the concept of healthy aging and the use of the principles of universal design as a support, resulting in good packaging not only for the elderly, but also for all.